The Bear and The Dragon : Jack Ryan Universe #11 - Clancy, Tom, 1947-; Muller, Frank, 1951-; HarperCollins (Firm) (New York : HarperCollins, 2000)
Jack Ryan is president and Russia is still trouble. Someone has tried to assassinate the head of the SVR (once known as the KGB). Was it a political opponent, a former KGB officer, the Russian mafia, or something far more dangerous?
Compact discs.
Sequel: The teeth of the tiger.
Sequel to: Rainbow six
Read by Frank Muller.
Keywords: Ryan, Jack (Fictitious character) -- Fiction; World politics -- Fiction; Presidents -- United States -- Fiction; International relations -- Fiction; United States -- Foreign relations -- Fiction; Adventure fiction; Audiobooks on CD; Political fiction